Pelatihan Bahan Pembelajaran Pada Guru-Guru Madrasah Pendidikan Diniyah Takmiliyah Kecamatan Rumbai Kota Pekanbaru - Tanjung, Abrar; Arlenny, Arlenny; Hamzah, Hamzah (Fakultas Teknik Universitas Lancang Kuning, 2021)
Educational unit-level curriculum for educational programs developed by each educational institution is expected to be able to adapt to the needs, conditions, and characteristics of students in their respective regions. KTSP can make educational institutions have the authority to develop various learning programs to achieve national education goals that still refer to the National Education Standards (SNP). Microsoft Office is a program used to create, edit, and type scripts. The partner group for Madrasah Pendidikan Diniyah Takmiliyah is located in Rumbai District, Pekanbaru city. The results of the discussion are obtained after the training is obtained above 85% can operate the Microsoft Office program and can create and compile a Learning Program Unit (SAP) in accordance with the curriculum standards of the Ministry of Religion.